PERBANDINGAN ANTARA MESIN BENSIN YANG BERTEKNOLOGI VVT-1 DENGAN PLATINA - SARAGIH, DARWAN EDIANTO (STMIK KAPUTAMA, 2019)
The high level of demand for vehicle users to have a car with a powerful engine but still fuel efficient and environmentally friendly has been the trigger for the emergence of ideal new technology with the name of the Timing-Intelligent variable, better known as VVT-i. The adoption of VVT-i technology into car engines also provides the advantages of the minimum maintenance costs that must be borne. Because tune-ups like valve settings etc. are no longer needed. The purpose of writing is to determine the performance of the otto engine with VVT-i technology and determine the power produced by VVT-i and platinum engines. For the same round of 3500 rpm, the power generated by VVT-i technology is 44,179 kW, while without VVT-i technology the power is 43,154, so the increase is 2.32%.From the relationship of engine speed and power, that power increases frequently with increasing engine speed. But after reaching maximum power at 6000 rpm, the power slowly decreases even though the engine speed continues to increase. For the same cycle of 3500 rpm, the fuel consumption of VVT-i technology is 251.5098 gr / kW, while for platinum the fuel consumption is 260.0889 gr / kw hours, resulting in a decrease of 3.41%. Engine performance increases frequently with increasing engine displacement, but after reaching maximum torque, torque slowly decreases even though the engine speed continues to increase. There is a significant difference in torque and fuel consumption between VVT-i technology with platinum engine at 5000 rpm rotation.